ABKK2203 Comparative politics - Malik, Maszlee (Open University Malaysia (OUM), 2016)
This text book is for learners taking the Bachelor of Political Science programme and those who are interested to learn about national and international issues affecting the governance of the international system. This module aims to cover theories and concepts such as political institutions, public policy, legislature and constitution, political and economic development. Contemporary issues that will be covered also include environmental problems and the link to interest groups and political parties. This module also consists of studies on government and politics in industrialised societies in the West and Asia, focusing on their legislature and executive process, political parties and voting behaviour.